Determinants of financial distress: Evidence from insurance companies in Ethiopia - Tekalign Negash Kebede; Getahun Deribe Tesfaye; Obsa Teferi Erana (Journal of Innovation and Entrepreneurship, 2024)
The issue of financial distress has received much attention of scholars because it harms firm financial and operational systems which could lead to insolvency. The objective of this study is to examine the determinants of financial distress in Ethiopian insurance companies. A panel dataset was obtained from 11 insurance companies which range from 2010 to 2021. The study used the "Altman's Z"-score model as a measure for financial distress. The pooled OLS regression results revealed that profitability (ROA), liquidity levels, insurers' size, earnings growth, diversification have negative and significant effect on financial distress. Moreover, inflation rate, claims ratio, leverage, and asset tangibility have positive significant impact on financial distress. The study will have implications for different stakeholders, such as managers, policy makers, shareholders, etc., in that firm-specific and macro-economic factors are essential for managing the status of financial distress.
Keywords: C33; F65; G22; M41; 650; "Altman's Z"-score; Ethiopia; Financial distress; Insurance companies; Pooled OLS